Strategi Promosi Pembiayaan Murabahah Bank Syariah di Indonesia - M. Miftahur Rahmat Isnaini; Siti Sofiah Rahmawati; Muhamad Zen; Fatmawati Fatmawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Murabahah Finance is one of the sharia bank financing products that is in great demand by customers because Murabahah adheres to the principle of buying and selling which is not too risky. Sharia banks are expected to increase public confidence in Murabahah products. To build this trust, a promotional strategy is needed. The method used in this research is a literature study, by collecting data from various sources such as academic journals, books and research reports related to murabahah. The results of the analysis show that the promotion strategy for murabahah financing of Islamic banks in Indonesia can be divided into several aspects, including direct marketing, marketing through mass media and online, as well as partnerships with other financial institutions, Sharia Banks in Indonesia and promotional strategies. Promotional strategies play an important role in marketing Islamic bank murabahah financing in Indonesia. By implementing appropriate promotional strategies, Islamic banks can increase public awareness, expand market share, and gain a competitive advantage in the Islamic banking industry.